IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DALAM UPAYA PENCEGAHAN KECELAKAAN KERJA PADA LINGKUP INDUSTRI DI KOTA SEMARANG - Atikah, Talia; Dwimawanti, Ida Hayu; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The author uses the theory advanced by Van Meter and Van Horn in analyzing the factors that hinder the implementation of SMK3. Lack of government attention on the implementation of Semarang, SMK3 on industrial companies that have a wide range of production equipment that can raise the risk of accidents in the workplace for their employees. Still emerging number of work accidents listed in the document reports on the Department of Manpower and Transmigration Semarang. The provision of the right of labor to obtain safety and health at work have not been fully supplied by the company. The results showed SMK3 implementation is not optimal, as it is called by the PP. 50 In 2012. There are many findings the actual discrepancy is not in accordance with auditing criteria SMK3 ranging from the commitment and policy, planning, implementation, and evaluation of a survey to review and increase SMK3 in the workplace.